The HOMME project – Human Origins in Mozambique and Malawi Environments: looking for our origin in the Mozambican karst - (:unkn) unknown (My University, 2022)
Mozambique is a crucial area for unravelling our evolutionary history, during the early phases of the Quaternary. Indeed,located at the southern end of the Great Rift between Southern and Eastern Africa, this area plays a key‐role in our understanding of the paleobiogeography of fauna documented in the fossil record of East and South Africa. The Human Origins in Mozambique and Malawi Environments – HOMME – project aims to identify evidence of early hominins in this area, which is under‐studied as compared to eastern and southern African regions, as well as to characterize the paleoenvironmental contexts in which the genus Homo emerged. This paper presents the results obtained during our first field season. We explored various karstic cavities located along the Buzi river and the Cheringoma Plateau (west and north off Beira). Our explorations reveal the potential of the Mozambican karst systems for providing new Plio‐Pleistocene paleontological evidence. In particular, we report various endokarstic deposits containing paleontological remains. These promising findings reveal the richness of this area and the fundamental role of the karst in trapping and preserving fossils. Accordingly, this project will certainly fill in a number of gaps in the paleobiogeography and paleobiology of early hominins.
Keywords: African Research